Application of Carrageenan, Guar Gum as Biodegradable Coating on Storage of Persimmons (Diospyros Kaki) - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2018)
Persimmon (Diospyros kaki) is fleshy fibrous tropical, deciduous fruit belonging to Ebenaceae family. Persimmon is classifed as a low-acid fruit, presenting titratable acidity. Persimmon is popular and widespread fruit that is enriched with many bioactive compounds, including polyphenols, terpenoids, steroids, flavonoids, carotenoids, minerals and dietary fiber. Although consumed fresh, losses that occur during persimmon storage are, to a large extent due to excessive ripening, loss of firmness, rot and the incidence of fruit peel browning. The fresh fruits are highly perishable and there are several problems related to their conservation, originating at harvest time when a series of processes begin that inﬂuence the quality of the product and its consequent loss. One way to increase the availability to the consumer, and even provide more value to the end product, is edible coating. An investigation on coating of Persimmon by using carrageenan and guar gum was investigated. Persimmon fruits which were coated with 0.75% carrageenan still maintained shelf-life until 30 days of preservation.Keywords: Persimmon, Coating, Carrageenan, Guar gum, Preservation, shelf-life.